The Sorcerer in the North - John Flanagan (London : Corgi Yearling, 2009)
Will is finally a full-fledged Ranger with his own fief to look after - but his new land is already under threat. The Grimsdell Forest is being haunted by eerie voices and the terrifying figure of the Night Warrior. Could this really be the work of sorcery? Joined by his friend Alyss, Will is suddenly thrown headfirst into an extraordinary adventure. As Will battles growing hysteria, traitors, and most of all, time, Alyss is taken hostage, and Will is forced to make a desperate choice between his mission and his friend.